The Contribution of Sonoelastography to the Diagnosis and Correlation of Strain Index Values with Pathological Subgroups in Fibroepithelial Breast Lesions - Fatma Can (Galenos Yayinevi, 2021)
Introduction:Fibroepithelial lesions are the most common benign lesions of the breast. When detected by mammography and ultrasonography (USG), the limitations of these examinations and the goal of diagnosing malignant lesions at an early stage may lead to off-label biopsies. Unnecessary biopsy procedures can be avoided by developing additional reliable methods to complement existing diagnostic procedures. For more accurate characterization of breast lesions, US elastography is used, which gives information about elasticity and deformability of the tissue. In our study, we aimed to determine the contribution of elastography to the diagnosis in the evaluation of fibroepithelial lesions of the breast with USG and to determine the relationship between strain index (SI) values and pathological subgroups.Methods:Our study included 160 lesions in 105 patients who were diagnosed with pathologically proven fibroepithelial lesion in the Radiology Clinic of İstanbul Training and Research Hospital between September 2013 and November 2014, or who were followed up for at least two years with no pathology and whose radiological appearance was interpreted in favor of fibroadenoma (FA). Voluntary consent form and ethics committee approval for the study were obtained from the patients. USG examinations were performed with a 13-18 MHz linear high resolution volumetric probe. Considering the color map obtained in the elastography evaluation, different measurements were made from the hardest areas in the mass.Results:In the sonoelastographic evaluation of fibroepithelial lesions, the median mean SI value was calculated as 3.30 (between: 0.35 and 28.80). The SI value was found to be higher in complex FAs than in other subgroups. It was observed that the mean size decreased as the age group got older. A statistically significant positive correlation was found between elastography stiffness index and size (p<0.0001, Pearson correlation index 0.643).Conclusion:We think that US elastography contributes to morphological USG findings in the evaluation of fibroepithelial lesions of the breast and can guide the biopsy decision correctly.